2012
DOI: 10.1530/rep-11-0338
|View full text |Cite
|
Sign up to set email alerts
|

Sperm arylsulfatase A binds to mZP2 and mZP3 glycoproteins in a nonenzymatic manner

Abstract: We have shown previously that sperm surface arylsulfatase A (ASA) of mouse, pig, and human is involved in sperm-egg zona pellucida (ZP) binding. By treating capacitated mouse sperm with A23187 to induce the acrosome reaction, we demonstrated by immunoblotting that ASA also existed in the acrosomal content and on the inner acrosomal membrane. Since mZP2 and mZP3 are known as sperm receptors, whereas mZP1 as a cross-linker of mZP2/mZP3, we determined whether purified ASA bound to mZP2 and mZP3 selectively. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 62 publications
(117 reference statements)
2
28
0
Order By: Relevance
“…Arylsulfatase A (ARSA), sperm surface protein, is obtained by epididymal transit and remains on the cell surface during capacitation . ARSA seems to bind to mouse ZP receptor 2 (mZP2) and mouse ZP receptor 3 (mZP3) . In addition, we found a tetraspanin family protein (CD9) that has only recently been described in mouse sperm.…”
Section: Discussionmentioning
confidence: 74%
“…Arylsulfatase A (ARSA), sperm surface protein, is obtained by epididymal transit and remains on the cell surface during capacitation . ARSA seems to bind to mouse ZP receptor 2 (mZP2) and mouse ZP receptor 3 (mZP3) . In addition, we found a tetraspanin family protein (CD9) that has only recently been described in mouse sperm.…”
Section: Discussionmentioning
confidence: 74%
“…Electrostatic analyses of the structural characteristics of ARSA have revealed the presence of an additional domain adjacent to the active site that could account for the ability of the enzyme to bind to the ZP when the active site being concurrently occupied with alternate substrates (Schenk et al, 2009). Furthermore, recent studies have indicated that mutation of the active site does not inhibit the ability of ARSA to bind to mouse ZP2 and ZP3 (Xu et al, 2012). The more modest reduction in sperm -ZP binding observed after incubation of human spermatozoa with anti-SPAM1 antibodies (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In an alternate experiment, immunofluorescence of CLU was performed on sperm that were bound to the zona(e) pellucida(e) (ZP) layer coated onto the surface of a glass slide. ZP used in this experiment were prepared from mouse ovaries as previously described (Xu et al 2012) and heat solubilized in 0.2 M sodium phosphate buffer, pH 6.8 at two ZP/µL. The solubilized ZP solution was plated into the middle of the well of a Thermo Scientific 8-well Diagnostic glass slide (Thermo Fisher Scientific) and allowed to air-dry.…”
Section: Immunofluorescence Localization Of Clu and Sed1 On Spermmentioning
confidence: 99%